Clinical profiles of people with dementia exhibiting with neuropsychiatric symptoms admitted to mental hospitals: A multicenter prospective survey in Japan. Issue 9 (26th July 2021) - Hozumi, Asami; Tagai, Kenji; Shinagawa, Shunichiro; Kamimura, Naoto; Shigenobu, Kazue; Kashibayashi, Tetsuo; Azuma, Shingo; Yoshiyama, Kenji; Hashimoto, Mamoru; Ikeda, Manabu; Shigeta, Masahiro; Kazui, Hiroaki
Abstract : Aims: Patients with severe behavioral and psychological symptoms of dementia (BPSD) are often admitted to mental hospitals, while, inpatient care could also lead to prolonged hospital stay. The present study aims to survey clinical profiles of patients who required inpatient treatment for BPSD, and then establish the criteria for introducing inpatient treatment through assessment by certified psychiatrists. Methods: We performed a prospective survey about clinical characteristics of people with dementia who required treatment of BPSD at 12 mental medical institutions. All patients were assessed by certified psychiatrists to determine the optimal treatment settings: outpatient or inpatient. The multivariate logistic regression analysis was performed to specify factors contributed to the judgement of clinicians. Subsequently, the receiver operating characteristic curve analysis was conducted to explore a score derived from the Neuropsychiatric Inventory to divide patients into outpatient or inpatient groups. Results: The present study included 386 patients, of which 242 were admitted to mental hospitals. BPSD were classified into four domains, and aggressive BPSD was significantly associated with assessment for inpatient treatment; the adjusted odds ratio was approximately 2 regardless of dementia severity. Furthermore, the composite score of agitation, irritability and aberrant behavior showed the highest area under the curve value (=0.706), which differentiated inpatients from outpatients with a sensitivity of 76% and a specificity of 54%. Conclusions: Aggressive BPSD was the risk factor for inpatient treatment. The composite score of the Neuropsychiatric Inventory subdomain‐related aggressive BPSD could be a screening tool to introduce inpatient treatment for BPSD. Geriatr Gerontol Int 2021; 21: 825–829 .